బంజారాల వివాహా అచార పద్ధతులు - Naik, Azmeera Silma (Andhra Saraswata Parishath, 2015)
This book tells us about the marriages and rituals of Banjaras
Bhanjarala Vivaha Achara Paddhatulu
Keywords: Telugu; Literature; Telugu; Telugu